PENYULUHAN TENTANG BEYOND USE DATE (BUD) PADA OBAT-OBATAN - Galih Pratiwi; Aninditha Rachmah Ramadhiani; Yudi Arina; Ulik Alta; Mayang Tari; Onny Indriani; Gerry Nugraha; Suprayetno (Bengkulu Institute, 2023)
Beyond use date (BUD) is the time limit for using a medicinal product after it has been prepared/prepared or afte the primary packaging has been opened/damaged. Primary packaging here means packaging that is in direct contact with medicinal ingredients, such as: bottles, ampoules, vials, blisters, etc. This community service activity aims to provide information and education to the public through outreach activities about Beyond Use Date (BUD). The methods used in this activity were counseling, material presentation, and distribution of leaflets/brochures to all the people who attended the BUD counseling event. It is hoped that service activities can be developed in several other places and that people can use drug rationally. Â Â Â